Agrarian legal status of individuals: conceptual issues - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to the analysis of the concept of the agrarian legal status of individuals as a complex and multifaceted formation within the system of agrarian law. Based on an analysis of doctrinal provisions, sources of international law, acts of Belarusian legislation and political and programme documents, the concept of the agrarian legal status of individuals is substantiated, combining three interrelated dimensions that determine the participation of individuals in agrarian legal relations of various types. The basis of the first, substantive, dimension of the agrarian legal status of individuals is the constitutional human right to adequate food. The author proposes to consider ensuring this human right as the goal of legal regulation of agrarian law. The second dimension of the agrarian legal status of individuals covers a set of rights, duties and responsibilities of individuals in connection with their agricultural activities. The third dimension of the agrarian legal status of individuals is related to the ensuring sustainable development of rural areas and realisation of the human right to a decent standard of living.